A sensitive and disposable graphene oxide electrochemical immunosensor for label-free detection of human immunoglobulin G - Watthanachai Jumpathong (2018)
© The Japan Society for Analytical Chemistry. In this work, a cost-effective and simple-to-prepare label-free electrochemical immunosensor was, for the first time, fabricated by modifying high-quality graphene oxide (GPO) onto a screen-printed carbon electrode (SPCE). The anti-IgG antibody was then covalently immobilized to the carboxylic group anchoring on the surface of GPO particles. Under the optimized condition, our newly developed immunosensor selectively bound to human immunoglobulin G (IgG), a model biomarker, with high sensitivity at a limit of detection of 1.99 ng mL-1, potentially sensitive enough for IgG detection at the pathophysiological level, and had a linear range of 2.5 to 100 ng mL-1. The proposed immunosensor also exhibited high reproducibility and regenerability, resulting in no significant change in electrochemical signals from different replicates of the electrode, and a robust electrochemical current after being subjected to alkaline base washing with several cycles. To this end, our immunosensor demonstrates ability as a promising diagnostic tool for clinical assessment. 2016